Sayyid Qutb’s approach to Qur’ónic exegesis: an analysis - Ali, Md. Yousuf; Osmani, Noor Mohammad (2015)
Sayyid Qutb (1906-1966) is one of the most influential Islamic scholars in the 20th century who has written many books and articles on Islamic thought in order to relate the Qur’Én and Sunnah with integrated approach to modern life. He started a revolutionary mission at a time when Western civilization was at the height of its intellectual, technological, economic and political power, and when almost the entire Muslim world was in the clutches of Western colonial rule. The clouds of gloom were cast upon the Muslims all over the world. In this situation of turmoil, he challenged the spell of Western thought and developed a new ÑIlm al-KalÉm to meet the intellectual challenge of the West. To achieve this goal, in 1948, Qutb began writing to present Islam as the only alternative in every aspect of life in the journal of al-Fikr al-Jadid (Sayyid Qutb). His major work is the tfsir fi Zilal al-Qur`an, which is an accumulation of his lifelong experiences and knowledge for modern educated readers. His tafsÊr is the combination of both al-tafsÊr bi-al-ma´thËr and al-tafsÊr bi-al-ra’y but some Muslim scholars have alleged that it is as al-tafsÊr al-siyÉsÊ (political tafsÊr). The aim of this study is, to focus on selected aspects of Qutb’s approach towards understanding the Qur’Én in his Qur’Énic exegesis. This study evaluates objectively and critically the selected aspects discussed by him to see whether or not he is deviant in his approaches. It also examines whether or not Qutb explains the Qur’Én using AÍÉdÊth, the views of the companions, asbÉb al-nuzËl, IsrÉiliyÉt and other sources. Last but not least, this study also analyses his responses to the theological and philosophical issues, and contemporary Islamic and Western thought.